Physicochemical Characteristics of Cucumber Sherbet on Various Pandan Wangi Juice Concentrations and Sweetener Types - Syarifa Ramadhani Nurbaya; Rima Azara; Andriani Eko Prihatiningrum; Lukman Hudi; Danya Mozza Elshiva (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2024)
Cucumbers can be processed into a frozen snack called sherbet. The problem with using cucumber in sherbet processing is its bland taste. Pandan wangi leaves (Pandanus amaryllifolius Roxb.) can be used to improve the flavor and aroma of cucumber sherbet. This study aimed to determine the effect of pandan wangi juice concentration and sweetener type on cucumber sherbet’s physical and chemical characteristics. The study used a factorial randomized group design consisting of 2 factors: the concentration of pandan wangi juice (5%, 10%, and 15%) and the type of sweetener (simple syrup, fructose, and honey). The physicochemical characteristics observed in this study include overrun, texture, color (L, a, b), melting time, total dissolved solids, vitamin C content, and total chlorophyll. The interaction between the concentration of pandan wangi juice and the type of sweetener significantly influenced the overrun of cucumber sherbet. The concentration of pandan wangi juice significantly influenced the texture, greenness (a-), yellowness (b+), and total chlorophyll. The type of sweetener significantly affects the yellowness (b+) value, melting time, and total soluble solids. The best treatment is pandan wangi juice with a concentration of 15% and fructose syrup as a sweetener type. Pandan wangi juice concentration and sweetener type can improve the characteristics of sherbet in terms of both physical and chemical properties. Cucumber sherbet combined with pandan wangi juice and certain sweeteners can be a healthy frozen snack.